Efforts to Change Clients' Negative Stigma to Improve the Spirit of Recovery at Ciamis BNNK in 2026 - Wijayanti Candra Ningrum; Didin Solehuddin; Iwa Budiana; Yandi Cahya Yundani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Negative stigma against drug abuse clients remains a major obstacle to recovery. Judgmental public perception can undermine clients' self-confidence, motivation, and enthusiasm for rehabilitation. This study aims to examine efforts to change negative stigma and improve recovery motivation at the Ciamis Regency National Narcotics Agency (BNNK Ciamis). The method used was a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that efforts include providing individual counseling. Furthermore, the role of counselors and a positive environment are crucial in rebuilding clients' self-confidence. Changing negative stigma through the right approach can increase clients' motivation and enthusiasm for optimal recovery.Keywords: Negative Stigma, Clients, Recovery